Food policy in 2018-2019: Growing urgency to address the SDGs - Fan, Shenggen (International Food Policy Research Institute, 2019)
2018 was a somber and unpredictable year, not only for food and nutrition security, but also for global political stability and international development. Many regions of the world faced rising rates of hunger and stagnation in tackling malnutrition, and rising trade protectionism and antiglobalism led to dramatic shifts in multilateral and bilateral relations. Amid these challenges, rural areas continued to find themselves in a state of crisis marked by a deepening cycle of hunger and malnutrition, persistent poverty, limited economic opportunities, and environmental degradation. However, the potential of rural revitalization and a focus on the role of food systems to address these challenges offer promise of meeting the Sustainable Development Goals by 2030. The opening chapter of the 2019 Global Food Policy Report reviews these major policy developments of 2018 and looks ahead to 2019.